Formation of various-axis-oriented wurtzite nuclei and enlargement of the a-axis-oriented region in AlFeN films deposited on Si(100) substrates. Issue 12 (25th May 2021) - Imada, Saki; Isshiki, Toshiyuki; Tatemizo, Nobuyuki; Nishio, Koji; Mamishin, Shuichi; Suzuki, Yuya; Ito, Katsuji; Nitta, Kiyofumi; Suga, Hiroki; Sekizawa, Oki; Tamenori, Yusuke
Abstract : A -axis-oriented single-crystal AlFeN grains grew from randomly oriented small wurtzite grains with deposition time on Si(100). (a) Deposition time dependence of Al K-edge XANES spectra. (b) Theoretical spectra. Abstract : Wurtzite AlN films with high Fe concentrations were deposited on Si(100) substrates using radio-frequency sputtering, and the growth process was investigated. X-Ray diffraction (XRD) analysis with parallel incident X-rays showed that a thick film (∼2.5 μm) had a non-polar a -axis orientation, similar to the films deposited on SiO2 glass substrates. Through powder XRD analysis, it was found that non-wurtzite fine crystals and/or amorphous materials formed during the initial stage of deposition, followed by wurtzite nucleation with various orientations of the axes, such as a, m, and r orientations. The XRD results also implied that the a -axis-oriented regions drastically increased with increasing film thickness. Scanning transmission electron microscopy (STEM) and energy-dispersive X-ray spectroscopy analyses suggested that one of the candidates for the non-wurtzite fine crystalline material was γ-Al2 O3 . STEM analysis also demonstrated that a -axis-oriented single-crystal grains grew from randomly oriented small wurtzite grains that increased in diameter with increasing deposition time. Al K-edge X-ray absorption near-edge structure results suggested that the electronic structure in the polar c -axis direction of wurtzite lying in the film plane developed with deposition time, thereby further supporting the findings of the XRD and STEM analyses.